(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This work aims to analyze the legal aspects that involve the autonomy of the will, informed consent and the moral and legal responsibility of the physician towards the patient, family members and society. It also analyzes the conditions in which the doctor-patient relationship has been affected by a new paradigm of interaction, in which the autonomy of the patient’s will assumes a preponderant role in decision-making regarding the treatment to be administered. It shows the challenges arising from the increase in medical information on the internet, which allowed the debate on the best treatment to be applied outside the office environment and, often mistakenly and dissociated from the technique, gain social networks, as seen in case of Covid-19. Through a case study, it demonstrates the conflict between the therapeutic need and the will of the patient in an advanced stage of the disease, out of therapeutic possibility.